Transmissão de risco entre os mercados de commodities energéticas e agrícolas - Medeiros, Rodrigo Rego (2024)
The study assesses the impact of the contagion effect on the price formation of a broad group of commodities. Using a Quantile VAR (QVAR) model with rolling windows, and a variation of the methodology from Diebold and Yilmaz (2009, 2012, and 2014), the spillover effect of innovations in various commodity markets - energy, food, beverages, raw materials, fertilizers, metals and minerals, and precious metals - was captured, offering a dynamic forecast both over time and across the price return distribution. Based on the decomposition of the forecast error of the commodity price return series, as proposed by Parkinson (1980), the analysis of monthly data from 1970 to 2023 reveals pronounced connectivity in the tails of the distribution, emphasizing the critical role of systematic risk in periods of extreme market turbulence.